Heat transfer and turbulent nanofluid flow investigation over microscale backward-facing step - Abed, Albuhamdan Sadeq Salman (2021)
Flow separation and re-connection play important roles in many different fields. The continued increase in functionality and compactness in these fields and devices such as the microchannel, micro heat-exchangers. In the present study, experimental and numerical simulation using computational fluid dynamics (CFD) is applied to study the steady-state convective turbulent nanofluids and hybrid /water. However, the nanofluid of Ga2O3/water enhances the heat transfer rate in comparison with CuO/water nanofluid. Overall, the results showed promising outcomes of utilizing nanoparticles in the separation flow to enhance the heat transfer to the industry that relies on the heat transfer as the main goal to achieve such as heat exchanger. nanofluids flow over two-dimensional (2D) microscale backward-facing step (MBFS) placed in a channel. In this research, the wall downstream of the channel was maintained at a uniform heat flux, while the straight wall that forms the other side of the duct was maintained at a constant temperature equal to inlet fluid temperature. The upstream wall and the step wall were considered adiabatic surfaces. The expected valid trend of step height (S) length scale is considered in the range of 200 ≤ S ≤ 500 μm for the numerical study. The Reynolds number (Re) range in the study of 5,000 ≤ Re ≤ 10,000. All the other walls including the step were considered adiabatic. The step height was S = 500 μm in the experimental study. Different types of nanoparticles such as CuO and Ga2O3 with a volume fraction ( of 1%≤ ≤4% are dispersed in the water. Moreover, hybrid nanoparticles of CuO and Ga2O3 with 4% volume fraction have been applied in this study. To ensure the purity of CuO and Ga2O3 nanoparticles SEM, particle size distribution, and XRD characterizations have been applied. The outcomes reveal that the gradients in the Nusselt number (Nu) inside the recirculation region increase by increasing the S. It also appears that increasing the S decreases the pressure-drop and Re. Heat transfer rate enhances with an increase in any of the parameters of volume fraction ( and Reynolds number (Re). Also, the friction factor has a significant consequence on the rate of heat transfer and characteristics of the flow at a constant Re. Besides, the outcomes revealed the friction factor increased by increasing the volume fraction. The hybrid nanofluids of Ga2O3-CuO /water have a higher value of Nu in comparison with Ga2O3/water and CuO.